Ifosfamide-Induced Metabolic Encephalopathy in 2 Patients With Cutaneous T-Cell Lymphoma Successfully Treated With Methylene Blue - Anusha Vakiti MD; Ravi Pilla MD; Muhamad Alhaj Moustafa MD; Jacinth J. Joseph MD; Aarthi G. Shenoy MD (SAGE Publishing, 2018)
Ifosfamide, an alkylating agent used in cancer treatments, can cause neurotoxicity. The clinical presentation can range from mild symptoms such as acute confusion to non-convulsive seizures, severe irreversible coma, and death. The benefit of methylene blue use in treating ifosfamide-induced metabolic encephalopathy is not well established. In this article, we present 2 cases of ifosfamide-induced metabolic encephalopathy responsive to methylene blue treatment.